A Great Desire: Autobiography in Louise Talma’s Three Madrigals - Leonard, Kendra Preston (Current Musicology, 2011)
American composer Louise Talma’s compositions are highly autobiographical, concerning, among other subjects, her conversion to Catholicism (Hound of Heaven , 1938), her frustration with teaching and the limited career choices available to women of her day (The Alcestiad, 1961), milestone events in her life and in those of her friends (Ave Atque Vale, 1989), and her reaction to the Vietnam War (Voices of Peace, 1973). In this article I examine ways in which Talma’s very early secular vocal works likely refer to another aspect of her life, namely, her love and desire for an erotic relationship with Nadia Boulanger. To that end, I read the music and text of Talma’s Three Madrigals(1929, texts by Sir Thomas Wyatt), and, lacking scores, the texts of her songs “La Belle Dame Sans Merci” (1929, John Keats), “Late Leaves” (1934, Walter Savage Landor), and “Never Seek to Tell Thy Love” (1934, William Blake), as a non-traditional form of autobiography, or what Caren Kaplan calls an “out-law genre” (Kaplan 1992:122). Little research has been published on Talma to date. The bulk of her scores and papers are held by the Library of Congress in the Louise Talma Collection, which contains recently processed materials including manuscripts, printed scores, correspondence, and reviews. Yale University’s Beinecke Rare Book and Manuscript Library holds in both its Thornton Wilder Collection and its Louise Talma Collection materials relating to Talma and Wilder’s collaboration on their opera The Alcestiad. While a great deal has been written about Boulanger, very little of that deals directly with her relationship with Talma. However, with the materials from the Library of Congress now available, if not completely catalogued, it is possible to study this relationship in more depth. Talma’s extant letters to and from Boulanger begin in 1929, but their frequent referencing of past events, meetings, and conversations also provides insight into the women’s earlier interactions.